Lighter and heavier initial loads yield similar gains in strength when employing a progressive wave loading scheme - Wood, P. P.; Goodwin, J. E.; Cleather, D. J. (Biology of Sport, 2016)
Progressive wave loading strategies are common within strength and conditioning practice. The purpose of this study was to contribute to the understanding of this strategy by evaluating the effectiveness of 2 wave loading bench press training programmes that differed only in the initial load that was used to start the first wave. Thirty-four resistance-trained men were divided into 2 groups and performed 2 training sessions each week for 20 weeks. One session consisted of 6 sets of 2 repetitions, while the other consisted of 5 sets of 5 repetitions. The load used was incremented by 2.5% of one repetition maximum (1RM) each week until the subject could no longer complete the programmed repetitions. At this point, the load was decreased, and then started to ascend again. The initial loads for the 2 sessions were 87.5% and 80% 1RM respectively for the heavier group, and for the lighter group were 82.5% and 75% 1RM. The subjects experienced a significant improvement in their bench press performance (higher load group: pre test = 106.5 kg ± 14.6, post test = 112.2 kg ± 12.4, p = 0.05; lower load group: pre test = 105.7 kg ± 14.1, post test = 114.3 kg ± 11.0, p = 0.05), but there was no difference in the magnitude of the improvment between the two groups. These results tend to support the common practical recommendation to start with a lighter load when employing a progressive wave loading strategy, as such a strategy yields similar improvements in performance with a lower level of exertion in training.